Effect of Sedation on the Neurological Examination of the Patellar and Withdrawal Reflexes in Healthy Dogs - Horsley, Kristen T.; Olby, Natasha J.; Mitchell, Mark A.; Aulakh, Karanvir S.; Gines, J. Alberto (Frontiers in Veterinary Science, 2021)
Introduction: Pain, temperament, fear, and anxiety can prevent safe and accurate evaluation of common neurologic reflexes in dogs. When sedation is used it is unknown how the neurological examination, and specifically patellar and withdrawal reflexes are affected, and, if present, how long any effect might last. The purpose of the study is to investigate the effect of sedation on the evaluation of select common limb spinal reflexes in healthy dogs. Material and methods: 14 healthy dogs with normal neurologic exams were included. After placing joint landmarks, patellar reflex, pelvic and thoracic limb withdrawal reflexes were tested. Joint angles were measured, obtaining reflex angle endpoint, change in angle, and change in time to reflex completion. These measurements were recorded at different time points: prior to sedation (awake timepoint), 15 and 30 minutes following administration of standardized sedation protocol of dexmedetomidine and butorphanol, and 15 and 30 minutes following administration of a standardized reversal agent, atipamazole. Results: For patellar reflex, stifle end angle increased from 91.5 to 108.55 degrees (p<0.0001) 15 minutes following sedation, and remained increased at 104.5 degrees (p<0.0001) 30 minutes following sedation. Stifle change in angle increased from 9.6 to 24.4 degrees (p<0.0001) 15 minutes following sedation, and remained increased at 20.85 degrees (p<0.0001) and 11 degrees (p=0.012) at 30 minutes sedation and 15 minutes reversal. Tarsal joint in pelvic withdrawal and elbow in thoracic withdrawal reflexes, did not differ in at any timepoint of sedation or reversal when compared with awake timepoint, for end angle or change in angle. The increases in end angle and change in angle for patellar reflex generated a change in time for patellar reflex from 0.12s (awake) to 0.129s (15min sedation) which was statistically significant (p=0.041). Change in time did not differ for pelvic withdrawal or thoracic withdrawal. Discussion/Conclusions: Reflexes were elicited in all dogs under sedation. Sedation does not affect the evaluation of the withdrawal reflex on any limb but improves the visualization of the patellar reflex in this group of neurologically normal dogs.